Religion as A Determinant of Voter Behavbiour: An Analysis Of The Relation Between Religious Inclination And Voting Pattern In Cross River State, Nigeria (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Religion and politics are two very important aspects of human society anywhere in the world. While religion addresses and conditions man’s spiritual balance, politics shapes the practice of religion and determine who gets what, when and how (Lasswell, 1958) in any given political setting. The belief in the supernatural can make people to resist any perceived attempt to distort one’s religious belief. An attempt to sustain one’s religion on the other hand can determine the way one acts in the electoral process. In other words, the notion that a favourable polity guarantees the liberty to exercise freely one’s religious rituals can influence the attitude and the way people act in deciding who should govern them. Religion and politics have come to be inseparable in man’s quest for political power. In some societies, religion has been exploited to promote ascendancy to state power. This study assesses the relationship between religion and voter behavior in Cross River State, Nigeria and whether religious consideration influenced the voting direction of electorates in the 2011, 2015 and 2019 general elections. The rise of Islamic fundamentalism and segregate Pentecostalism in Nigeria’s religious behaviour justifies this study. The research hypothesizes that religious inclination tends not to have significant effect on the voting pattern in Cross River State. Data was collected through a questionnaire from Christian churches and mosques in five locations in the state. Respondents sample size of 1,000 was got from the five locations covering the three senatorial districts. Data generated was analysed with frequency count, percentages and barcharts. The results show that respondents voted along religious lines in the 2011, 2015 and 2019 general elections. Factors such as adherence to religious principles, pressure from religious superiors, denominational considerations accentuated this behavior. The study recommends among others that voter education should be intensified by civil society organizations on the danger of voting along with religious considerations.